Post-quantum verifier-based three-party password authenticated key exchange protocol - Huanhuan LIAN; Huiying HOU; Yunlei ZHAO (Tongxin xuebao)
In view of the fact that server stored the passwords directly in plaintext, there was a risk of server compromise, and two-party PAKE protocol was not suitable for large-scale communication systems, a three-party verifier-based password authenticated key exchange protocol from lattices was proposed.Hashing scheme and zero-knowledge password policy check were combined to realize the generation of verifier and the password checking.A novel verifier-based 3PAKE protocol was constructed by using CCA-secure public-key encryption from lattices, which realized mutual authentication.Security and performance analysis shows that the proposed protocol has better advantages in communication efficiency and security.